Development Of Uv Light And Water Filtering System During Flooding Event - Baharin, Lailatus Syarah Kamarol (Universiti Sains Malaysia, 2019)
Due to the rapid growth of development, there are many economic activities carried out in order to develop the nation. The activities done has led to many type of pollutant especially river water pollution. This is because, all of the activities will use the water resources to do their work and it will discharge to the river at last. The pollution usually contains variations of the organic and also inorganic pollutants which always exceed the permissible limit of drinking water standard. In order to reduce or treat the pollutants, the applications of adsorbents for river water have been studied for years. But, among the studies, there is no data available on the development of adsorbent from activated carbon (AC) and limestone (GLS) combined with the UV light in treating water. In this study, the adsorbent were synthetized for the adsorption of Colour and turbidity while the UV light was synthetized for the treatment of the E.coli in the river water. The effect of the adsorbent dosage was investigated. The study about the suitable model of isotherm also been covered and at the last part, the study of fixed-bed column was done. In this study, the sample was collected from Kerian River which has been taken at three parts of the river, at the downstream, middle and also the upstream. Then, the characterization for each of the part was done and it needs further treatment to be used as drinking water. The results have been identified, from the adsorbent dosage of limestone, the highest percentage of removal efficiency for Colour and turbidity was determined at 76% and 89%. While for the adsorbent dosage of activated carbon, the highest percentage of removal efficiency for Colour and turbidity was determined at 37% and 61% respectively. For the adsorption isotherm model, it has been defined that the Langmuir isotherm model was found well fitted to the equilibrium adsorption data. Based on the breakthrough curve, both of the breakthrough point for Colour, turbidity and e.coli for both adsorbent were less than 60 minutes respectively.